Sovremennye tendencii v sfere informacionno-kommunikacionnych technologij v olimpijskom sponsorstve - Miah, A.; Yarmoliuk, E. (Science in Olympic Sport, 2017)
The article deals with the peculiarities of employment of information and communication technologies in the activities of Olympic sponsors, such as software and hardware and technical aids and devices, operating on the basis of microprocessor computational tools, modern tools, and systems for transmission and exchange of information divided in three groups: networks, terminals and services. It was found that the use of new technologies significantly improves the effectiveness of the implementation of sponsorship programs in the Olympic sport, ensuring its economic independence. It was shown that the companies that occupy leading positions in the field of information communications play a significant role in providing sponsorship support. It was found out that the main trends in the Olympic sponsorship are the introduction and demonstration of modern information and communication technologies in the course of preparation and holding of the Summer and Winter Olympics Games.